A NetLogo implementation of the norms and meta-norms game: Behavior Analysis meets Agent Based Modeling (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This work aims to fill in the gap between cultural behavior analysis and recent computational approaches to the study of social dynamics. We first introduce a game-theory infused understanding of norms and metanorms evolution and how agent-based models are used to simulate and analyze the emergency of normative phenomena. Then we argue that this method is in line with the cultural behavior analysis approach to the evolution of culture, offering a common framework for further theoretical and heuristic developments for researchers in the field. We proceed by outlining Axelrod´s Metanorms Model, followed by a tutorial on its implementation with NetLogo programming language. Finally, two experiments are carried out using this framework, and the implications of the results, along with future direction of research, are discussed from a Skinnerian perspective.
Keywords: agent-based model; norms; metanorms; social simulation; behavior analysis